Synthesis and Surface Characterization of Magnetite-Titania Nanoparticles/Polyamide Nanocomposite Smart RO Membrane. (2015) - Tayefeh, A.; Mousavi, S.A.; Wiesner, M.; Poursalehi, R.
Abstract: In the water desalination technology, utilizing nanocomposite membranes have been an interesting approach to improve the water permeability and rejection properties of conventional reverse osmosis (RO) membranes. In this research, effects of magnetite (Fe3 O4 ) and titania (TiO2 ) nanoparticles by loading in trimesoyl chloride (TMC) organic solution and in metaphenylene diamine (MPD) aqueous solutions on the surface characteristics of polyamide layer have been investigated. Also, the morphology and EDS line and map analysis of Fe3 O4 coated PSf layer and in-situ reduced Fe3 O4 by impregnation of precursors inside PSf layer after formation of PA top coat, have been considered. The morphology, dispersion of nanoparticles, surface bonds of magnetite and titania nanoparticles with polyamide and hydrophilicity of magnetic nanocomposite RO membrane has been taken into account in each method by scanning electron microscopy (SEM), attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR), X-ray diffraction (XRD) and contact angle measurement. Trace of nanoparticles inside membrane cross section has been analyzed by energy dispersive spectroscopy (EDS) method. The samples were implemented to the different magnetite nanoparticle weight percent caused to the variation of surface energy, contact angle, roughness and polyamide layer free bonds. In addition the optimum concentration of magnetite nanoparticles for improvement in surface properties of high efficiency reverse osmosis membrane was obtained. The results can provide a versatile technique for fabrication of high efficiency magnetic responsive nanocomposite smart RO membranes.